2004
DOI: 10.1098/rsbl.2003.0157
|View full text |Cite
|
Sign up to set email alerts
|

Development of flight performance in the brown booby

Abstract: How do birds acquire flight skills after fledging? This issue is important, as it is closely related to variation in the duration of offspring care, the causes of which remain unknown. In this study, we raised hatchling brown boobies, Sula leucogaster, and attached an acceleration data logger to each bird at fledging to record its movements. This allowed us to quantify precisely the time spent flapping, gliding and resting. The duration of foraging trips and proportion of time spent gliding during flight incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 12 publications
(13 reference statements)
5
96
1
3
Order By: Relevance
“…Conventionally, it is not believed that invertebrates such as insects are capable of showing motor learning based on sensory input or from experience, as has been found in vertebrates (Yoda et al, 2004). Undoubtedly, most flight behaviour in Drosophila seems to be genetically predetermined, because naive flies show seemingly 'normal' flight behaviour when randomly released into the laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventionally, it is not believed that invertebrates such as insects are capable of showing motor learning based on sensory input or from experience, as has been found in vertebrates (Yoda et al, 2004). Undoubtedly, most flight behaviour in Drosophila seems to be genetically predetermined, because naive flies show seemingly 'normal' flight behaviour when randomly released into the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, flight in birds is assumed to be correlated with maturation and thus with the development of muscles and neurons, without any learning taking place (Grohmann, 1939). A recent study on the brown booby Sula leucogaster, however, showed that flight duration decreases and the proportion of time spent gliding increases, with the number of days since fledging, indicating that flight becomes more efficient with experience in this seabird (Yoda et al, 2004). Motor skills in insects and other invertebrates, by contrast, are still widely recognised as being predominantly innate fixed-action patterns.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…By 'learning', we here mean a change in behaviour resulting from experience [9]. In particular, learning of foraging techniques during immaturity has been studied in primates [10], bears [11], dolphins [12], seabirds [3,13,14], and insects (e.g. [15]).…”
Section: Introductionmentioning
confidence: 99%
“…The study of learning behaviours during immaturity raises important questions about innate and learned behaviours, and the evolutionary [16], social [17] and memorization [9] processes involved. Learning processes can result from individual experience [3,14,15] or can also imply a transfer of information between conspecifics: this is generally considered as 'social learning' [10 -12].…”
Section: Introductionmentioning
confidence: 99%